PENGARUH PROGRAM KESELAMATAN DAN KESEHATAN KERJA (K3), LINGKUNGAN KERJA DAN KEDISIPLINAN TERHADAP KINERJA KARYAWAN PADA PT. WIJAYA KARYA Tbk PEKANBARU - Dwiky Syahputera; Machasin Machasin; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research is conducted at PT. Wijaya Karya Tbk Pekanbaru which is have address in Jl. General of Sudirman, Pekanbaru. Amount of sampel in this research is counted 85 people or totalize the overall of population. Intake of sampel relied on census method. While to analyse data, writer use doubled linear regression method constructively peripheral of SPSS Version 17.0.Pursuant to result of test of F known that f value count 15.172, bigger than F of is tables of 3.240 with storey, level of Sig equal to 0.000 < 0.05 meaning h0 refused and Is ha accepted. This matter indicate that Safety variable and health of activity (K3), environmental of discipline and activity by together have an effect on signifikan to employees performance at PT. Wijaya Karya Tbk Pekanbaru. Pursuant to result of test of known that that Safety variable and health of activity (K3), environmental of discipline and activity by parsial have an effect on signifikan to employees performance at PT. Wijaya Masterpiece of Tbk Pekanbaru.Contribution influence of Safety variable and health of activity ( K3), environmental of discipline and activity to employees performance at PT. Wijaya Karya Tbk Pekanbaru equal to 53,6 %, while the rest 46.4 % influenced by other variable which do not check in this research.Keywords : Performance, Safety and Health, Environmental, Discipline.